Performance Of Solar Air-Conditioning System Using Heat Pipe Evacuated Tube Collector - Moorthy, M. (2010)

(untitled)
This paper presents the performance of solar air conditioning system using heat pipe evacuated tube collector. The currentsolar airconditioning system is not competitive with electricity driven air conditioning system due to their high investment cost.The electricity driven chiller has higher peak load during the daytime whereassolar air conditioning system were converting the low grade solar energy into high grade solar energy and protects the environment with energy conservation.Meanwhile, its overall thermal energy conversion efficiency is relatively low compared to conventional air conditioning.The experiment was carried out for 10 working hours from 08:00 to 18:00during June 2010. The obtained results show that the system technically viable. The heat pipe evacuated the tube efficiency, coefficient of performance (COP) of the double effect lithium bromide (LiBr) and water (H2O) absorption chiller, and the overall system efficiency were analysis. It can be seen that the solar collector efficiency varies from 26 to 51% during daytime and stored energy can be used for several hours during nighttime. The absorption chiller COP varies from 0.7 to 1.2 throughout the experiment and overall system efficiency varies from 27 to 48%. There is further research needin order to improve the overall system efficiency and it iseconomically profitable.